Determinants of attitudes to carnivores: implications for mitigating human–carnivore conflict on South African farmland. Issue 2 (8th May 2014) - Thorn, Michelle; Green, Matthew; Marnewick, Kelly; Scott, Dawn M.
Abstract: Human–wildlife conflict is increasingly prevalent, particularly in relation to carnivores in non-protected areas of Africa. Quantifying the attitudes of land owners towards carnivores and understanding the factors that influence these attitudes are instrumental in conservation planning and reducing persecution-related threats to carnivores. However, information about attitudes to carnivores in Africa, and South Africa in particular, is scarce. To obtain such data we interviewed 170 commercial game and livestock farmers in two ecologically important rural areas of northern South Africa. Responses to statements about carnivore management, stock protection and predation were generally positive. However, 62% of respondents believed carnivores to be financially damaging and 35% thought them overly abundant. Many respondents (41%) were unwilling to tolerate even low levels of predation and considered persecution of carnivores to be the cheapest form of stock protection (31%). Attitudes were significantly more positive among respondents who did not kill carnivores than among those who did. Generalized linear regression coupled with information-theoretic analysis showed that attitudes to carnivores were determined by a combination of cultural and land-use attributes more than by economic factors such as stock holdings or predation losses. The results elucidate potential targets for mitigation activities and facilitate the development of communication, education and extension activities specifically designed to appeal to intended recipients and address prevalent motives for persecuting carnivores.